US-Grenada Relations - Williams, G. author. aut Link
XII, 298 p.
Keywords: Why did the world's strongest power intervene militarily in the tiny Commonwealth Caribbean island of Grenada in October 1983? This book focuses on United States-Grenada relations between 1979 and 1983 set against the wider historical context of US-Caribbean Basin relations. It presents an in-depth study of US policy during the Carter and Reagan presidencies and the deterioration of relations with the Marxist-Leninist People's Revolution Government (PRG) of Grenada. It considers in detail the murderous internal power struggle that destroyed the PRG and the decisionmaking process that resulted in a joint US-Caribbean military intervention.